2002
DOI: 10.1002/glia.10169
|View full text |Cite
|
Sign up to set email alerts
|

Role of enteric glial cells in inflammatory bowel disease

Abstract: Enteric glial cells (EGCs) represent an extensive but relatively poorly described cell population within the gastrointestinal tract. Accumulating data suggest that EGCs represent the morphological and functional equivalent of CNS astrocytes within the enteric nervous system (ENS). The EGC network has trophic and protective functions toward enteric neurons and is fully implicated in the integration and the modulation of neuronal activities. Moreover, EGCs seem to be active elements of the ENS during intestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
154
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(163 citation statements)
references
References 117 publications
4
154
0
2
Order By: Relevance
“…The P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , and P2Y 11 receptors are coupled to stimulation of phospholipase C (PLC). P2Y 12 , P2Y 13 , and P2Y 14 receptors are negatively coupled to adenylyl cyclase (AC); the P2Y 11 receptor is positively coupled to AC. Abbrachio et al [1] provide an update on molecular mechanisms, pathophysiology, and therapeutics of P2Y receptors.…”
Section: Purinergic Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…The P2Y 1 , P2Y 2 , P2Y 4 , P2Y 6 , and P2Y 11 receptors are coupled to stimulation of phospholipase C (PLC). P2Y 12 , P2Y 13 , and P2Y 14 receptors are negatively coupled to adenylyl cyclase (AC); the P2Y 11 receptor is positively coupled to AC. Abbrachio et al [1] provide an update on molecular mechanisms, pathophysiology, and therapeutics of P2Y receptors.…”
Section: Purinergic Receptorsmentioning
confidence: 99%
“…Antagonists include N6-(2-methylthioethyl)-2-(3,3,3-trifluoropropylthio)-βγ-dichloromethylene-ATP (AR-C6931MX or cangrelor), AZD6140, and active metabolites of clopidogrel and prasugrel. The P2Y 13 receptor is found in nerve cells and immunocytes and is activated similar to the P2Y 12 receptor, but is selectively blocked by 6-(2′-chloro-5-nitro-azophenyl)-pyridoxal-α5-phosphate (MRS2211). The P2Y 14 receptor is activated by UDP-glucose.…”
Section: Purinergic Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…44 In fact, experimental human and animal studies have shown that enteric glial cells may also be involved in intestinal inflammation, 45,46 enteric neurotransmission [47][48][49] and, importantly, are essential for the homeostasis of enteric neurons. 50 With respect to this last aspect, a recent study showed that enteric glia disruption may alter the neurochemical coding of enteric neurons in an experimental animal model.…”
Section: Discussionmentioning
confidence: 99%